The Poverty of Data in Africa: Why the Continent Needs More Bacon. (December 2019) - Kinyondo, Abel; Pelizzo, Riccardo; Bekenova, Kristina
Even if data analysis in Africa has allegedly allowed analysts to expand the boundaries of inquiry, social science research in the continent has been hindered by several problems. Some of these problems could be viewed as subcategories of the idols that Francis Bacon had identified. We show in the present article that bad data lead to bad analyses, which in turn lead to misleading interpretations and misleading interpretations lead to a type of knowledge that is distinctively different from real and objective knowledge. We conclude by recommending that to avoid most, if not all, of the research problems in Africa, social science researchers should realize that social phenomena are embedded in an infinite web of relations from which only true meaning can emerge. It follows that, to gain a proper appreciation of such network of relations, social phenomena must be approached at various levels from different perspective.